Perancangan Pembangkit Listrik Mikrohidro 30 Kw Untuk Suplai Listrik Area Wisata di Desa Girimulyo Ngargoyoso, Karang Anyar, Jawa Tengah - Ridwan Leksana; Bambang Widodo; Eva Magdalena Silalahi; Judo Ignatius Nempung (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2023)
describe a power plant that employs the flow of water as its source of propulsion. An investigation must be conducted on the subject, specifically water, in order to gain an understanding of its potential prior to beginning the design process for a micro hydro producing unit. The micro hydro power plant in the village of Girimulyo serves as both a source of electricity and a popular tourist and educational destination for the community. Data were gathered from the observations, including the water discharge (Q=0.2 m3/s) and the head/height of falling water (H=22.09 m). obtaining information depending on flow rate and heightof the falling water may already be determined, allowing the Pelton type Micro Hydro turbine to be selected as the drive unit. whereas the 30kW turbine is intended to produce electricity. The major parts of the Pelton type turbine were constructed with wheel diameter D = 448mm, number of nozzles 2, shaft diameter d = 38mm, and gearbox based on the results of the data obtained. flat belt having a 1:1 transmission ratio.